(untitled) (Journal of Parents and Teachers, 1997)
The article describes the plight of parents with adolescents who exhibit problematic behaviors, such as lying, stealing and defying authority. Parents feel desperate and have tried various strategies without success, creating a chaotic home environment. The need for parents to take responsibility for their children’s decisions and stop giving in to their demands is emphasized. Finally, we reflect on the loss of control and the search for balance in the family relationship.